Peran Guru Muslimah Dalam Pendidikan Karakter di SMP-IT Darul Istiqamah Maros - Syamsiah Saad; Ahmad Hakim; Rosmiati (Journal of Gurutta Education, 2022)
This study aims to describe the implementation of character education and the role of Muslim teachers in SMP-IT Darul Istiqamah Maros. This research is qualitative descriptive research. The location of this research was carried out at SMP IT Darul Istiqamah. sources of research data using primary and secondary data. Data collection techniques use observation, interviews, and documentation methods. The data analysis technique was carried out descriptively with the stages of data collection, data reduction, data presentation, and drawing conclusions and verification. Based on the results of the analysis of this study, it was found that the implementation of character education at SMP-IT Darul Istiqamah Maros went well, including the formation of students' religious character, character building for students themselves, and character building for others. The role of Muslim teachers is very important in character education in Indonesia. SMP-IT Darul Istiqamah Maros. This important role makes Muslim teachers play a role as a source of learning, a role in guiding, being an example, and acting as an advisor